Mathematical Critical Thinking Profile-based Ennis and Gardner's Theory of Multiple Intelligences - Mujib Mujib; Sukestiyarno Sukestiyarno; Hardi Suyitno; Iwan Junaedi (AlphaMath : Journal of Mathematics Education, 2022)
Mathematical thinking is absolutely essential for school learning at all levels, including the HOT and LOT. The purpose of this study is to characterize the mathematical critical thinking ability pattern using Ennis and Gardner's theory of multiple intelligences. The research conducted in this study is qualitative. Purposive sampling was used in this study, which was conducted at SMPN 29 Bandar Lampung. Five people were involved in this study. To collect data, the researcher used a mathematical critical thinking essay test, a multiple intelligence questionnaire administered by a psychology expert, and in-depth interviews. Techniques for data analysis include data reduction, data visualization, inference, and verification (conclusion drawing and verification). The triangulation technique is used to find the truth of the data. The findings indicated that students were able to articulate the steps involved in developing mathematical critical thinking abilities. Additionally, students are more critical when it comes to problem-solving and approach the problem appropriately. Students provide direct responses rather than generalizations. Mathematics-related critical thinking patterns are frequently inductive.